2002
DOI: 10.1073/pnas.032480699
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic solution of the cylindrical nonlinear Poisson–Boltzmann equation at low salt concentration: Analytic expressions for surface potential and preferential interaction coefficient

Abstract: The analytic solution to the nonlinear Poisson-Boltzmann equation describing the ion distributions surrounding a nucleic acid or other cylindrical polyions as a function of polyion structural quantities and salt concentration ([salt]) has been sought for more than 80 years to predict the effect of these quantities on the thermodynamics of polyion processes. Here we report an accurate asymptotic solution of the cylindrical nonlinear Poisson-Boltzmann equation at low to moderate concentration of a symmetrical el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 36 publications
(47 reference statements)
5
49
0
Order By: Relevance
“…3 C, for instance). Similar depletion has also been observed in PB calculations by Misra and Draper (30), Ni et al (31), and Shkel et al (32).…”
Section: Range Of Validitysupporting
confidence: 87%
“…3 C, for instance). Similar depletion has also been observed in PB calculations by Misra and Draper (30), Ni et al (31), and Shkel et al (32).…”
Section: Range Of Validitysupporting
confidence: 87%
“…The condensation model has been verified by experiment and extensive Poisson–Boltzmann calculations. The latter have shown that short oligonucleotides deviate somewhat owing to so-called end effects (the ends of a duplex have a lower charge density than those in the interior) suggesting that these theoretical values would overestimate the experimental values for short oligonucleotides ( 204 , 205 ). More recently, Manning ( 114 , 115 ) has shown that even a spherical charge distribution will condense ions, depending on the actual charge density, and also on the ionic strength, albeit less than a cylinder.…”
Section: Ion Binding and Solvationmentioning
confidence: 97%
“…In this work, we consider the [49,50]. If the polymer backbone is treated as a cylinder, the effective, renormalized charge density of such a cylinder with ξ > 1 is then…”
Section: B Charge Densities and Counterion Condensationmentioning
confidence: 99%